Electronic Band Structure, Density of States, Phase Transitions, Metallization and Superconducting Transition of KBr under High Pressure - Ramola, Y.; Louis, C. Nirmala; Amalraj, A. (Orbital: The Electronic Journal of Chemistry, 2020)
The results of a full potential linear muffin-tin orbital (FP-LMTO) study on the electronic properties of ionic insulator potassium bromide (KBr) under pressure is presented. The phase transition pressure at which the compound undergoes structural phase transition from NaCl to CsCl structure is predicted from the total energy calculations. The ground state properties and band gap values are compared with the experimental results. At normal pressure KBr is a direct band gap insulator. In KBr, the metallization occurs through indirect closing of the band gap between G and H points at the reduced volume V/Vo=0.45 (CsCl structure), the corresponding metallization pressure is 1.274 Mbar. On further increase of pressure, KBr becomes superconductor, and this material comes under the class of electron-phonon-mediated high pressure superconductor. The superconducting transition temperatures (Tc) of KBr is obtained as a function of pressure for both NaCl and CsCl structures. The highest Tc estimated is 5.911 K and the corresponding pressure is 5 Mbar in the NaCl structure and 0.897 K in the CsCl structure. It is also confirmed that the metallization, structural phase transition and onset of superconductivity do not occur simultaneously in ionic compounds. DOI: http://dx.doi.org/10.17807/orbital.v12i2.1401